Correcting for Measurement Error in Food Demand Estimation - Brester, Gary W.; Wohlgenant, Michael K. (The Review of Economics and Statistics, 1993)
Use of disappearance data as proxies for actual consumption causes inconsistent estimates of own-price retail demand elasticities. A system of equations describing consumer, processor, and producer behavior is used to consistently estimate the retail demand elasticity for beef using available data while avoiding the restrictive assumption of fixed input proportions implicit in disappearance data. This approach yields an estimate of the own-price retail demand elasticity for beef of -0.45, which is more inelastic than the estimate (-0.66) obtained using a traditional approach. The methodology is applicable to other food commodities for which disappearance data serve as proxies for actual consumption. Copyright 1993 by MIT Press.